VELOCITY OF THE OFFENSIVE TECHNIQUE OF THE KARATE FOR THE MIXED MARTIAL ARTS FIGHTER: A SYSTEMATIC REVIEW - Marques Junior, Nelson Kautzner (Revista Observatorio del Deporte, 2015)
The objective of the systematic review was to present the velocity of the offensive techniques of the karate. This study followed the systematic review methodology proposed in PRISMA statement. The studies were identified in electronic databases during January of 2012 to May of 2015. Inclusion criteria of the articles were evaluated under the following search strategies: (1) type of participants, (2) type of task and (3) type of result. The researcher selected 24 studies that were included in this systematic review. The results of the study were the following: the best linear velocity of the punch was the gyaku zuki (13 m/s), the 2nd best linear velocity was the oi zuki (10 m/s) and the last position was the kizami zuki (7,1±1,88 m/s). The best linear velocity of the kick was the yoko geri kekomi (41 m/s), the 2nd best linear velocity was the mae geri keage (19,3 m/s) and the 3rd position was the mae geri kekomi (15,76±5,45 m/s). The study determined the linear velocity and the angular velocity of some joints of the body during the karate attack. The linear velocity of the hip, knee and of the ankle during the mawashi geri kekomi attack was faster than the return of the leg. The gyaku zuki tchudan had a higher angular velocity of the elbow (1483±172,9º/s) than the same joint of the kizami zuki tchudan (164,79º/s). The systematic review determined that the punch velocity (0,166 to 0,095 s) was higher than the kick (0,68 to 0,12 s). The systematic review determined that the kizami zuki tchudan was the fastest punch (0,11 to 0,096 s) and the mawashi geri tchudan was the fastest kick (0,13 to 0,12 s). In conclusion, the study of the velocity of the karate attack is important for the coach guide the MMA fighter.